2018
DOI: 10.1186/s12871-018-0570-0
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effect of Ropivacaine combined with Dexmedetomidine on brachial plexus block

Abstract: BackgroundThis randomized controlled study investigated the analgesic effect of ropivacaine in combination with dexmedetomidine versus ropivacaine alone on brachial plexus block to provide alternative anesthetic means for upper limb trauma surgery.MethodsTotally 114 patients who received upper limb surgeries under brachial plexus block anesthesia in our hospital from February 2013 to July 2015 were enrolled. The patients were randomized to ropivacaine alone (the control group) or ropivacaine combined with dexm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 3 publications
1
19
1
Order By: Relevance
“…Epidural or perineural DEX has been used in the range of 0.5~1 μg/kg without any incidence of neurological deficits [1820]. Even a higher dose (150 μg) DEX was added to ropivacaine for interscalene brachial plexus blocks, there were no acute or delayed neurological sequelae, and no significant adverse events [13]. It is reported that the addition of 1 μg/kg DEX to bupivacaine for caudal block has less adverse effect on the cardiovascular system in pediatrics [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidural or perineural DEX has been used in the range of 0.5~1 μg/kg without any incidence of neurological deficits [1820]. Even a higher dose (150 μg) DEX was added to ropivacaine for interscalene brachial plexus blocks, there were no acute or delayed neurological sequelae, and no significant adverse events [13]. It is reported that the addition of 1 μg/kg DEX to bupivacaine for caudal block has less adverse effect on the cardiovascular system in pediatrics [21].…”
Section: Discussionmentioning
confidence: 99%
“…Bhardwaj et al found that DEX plus ropivacaine for the surgical wound infiltration significantly alleviated postoperative pain and decreased the dose of rescue analgesic in patients undergoing lower segment cesarean section [12]. It is also shown that DEX added to ropivacaine extends the duration of brachial plexus blocks and improves postoperative pain [13]. When DEX is intravenously administrated during laparoscopic surgery, it significantly blunts stress response related to surgery and maintains haemodynamic stability [5].…”
Section: Introductionmentioning
confidence: 99%
“…Epidural or perineural DEX has been used in the range of 0.5~1 µg/kg without any incidence of neurological deficits [18][19][20]. Even a higher dose (150 µg) DEX was added to ropivacaine for interscalene brachial plexus blocks, there were no acute or delayed neurological sequelae, and no significant adverse events [13]. It is reported that the addition of 1 µg/kg DEX to bupivacaine for caudal block has less adverse effect on the cardiovascular system in pediatrics [21].…”
Section: Discussionmentioning
confidence: 99%
“…Bhardwaj et al found that DEX plus ropivacaine for the surgical wound infiltration significantly alleviated postoperative pain and decreased the dose of rescue analgesic in patients undergoing lower segment cesarean section [12]. It is also shown that DEX added to ropivacaine extends the duration of brachial plexus blocks and improves postoperative pain [13].…”
Section: Introductionmentioning
confidence: 99%